1990
DOI: 10.1007/bf00262257
|View full text |Cite
|
Sign up to set email alerts
|

Germ cell tumors of the thalamus and the basal ganglia

Abstract: Two cases of germ cell tumors (GCTs) of the basal ganglia are presented and 40 previously reported cases are reviewed. The incidence of GCTs of the basal ganglia and thalamus was estimated as less than 14% of all intracranial GCTs. All patients except for two (95%) were male, aged 7-19 years. The clinical course was usually slow. The major symptoms were hemiparesis, mental deterioration such as dementia or character change, precocious puberty, diabetes insipidus, oculomotor palsy, speech disturbance, and hemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 17 publications
2
74
0
1
Order By: Relevance
“…17,18) The most common symptoms in these patients were hemiparesis and cognitive dysfunction, which are nonspecific signs of involvement of subcortical structures. Only 4 patients without suprasellar lesions on MR imaging manifested diabetes insipidus, a possible clue for a preoperative diagnosis of germinoma.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…17,18) The most common symptoms in these patients were hemiparesis and cognitive dysfunction, which are nonspecific signs of involvement of subcortical structures. Only 4 patients without suprasellar lesions on MR imaging manifested diabetes insipidus, a possible clue for a preoperative diagnosis of germinoma.…”
Section: Discussionmentioning
confidence: 97%
“…5,6) Some basal ganglia germinomas are associated with hemispheric atrophy. 5,[7][8][9]11,15,17,19) The neuroimaging findings are usually subtle in the early stage and clinical manifestations are not specific, so diagnosis of germinoma in these regions is not easy. 1,5,7,15) We report 2 cases of germinoma in which the first magnetic resonance (MR) imaging revealed hemispheric atrophy that included the basal ganglia and follow-up MR imaging performed 12 and 23 months later disclosed new extra-ganglial lesions, and review reported cases of germinoma with hemispheric atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Ten percent of intracranial germinomas occur in offmidline locations such as the basal ganglia, thalamus or internal capsule (1,2). Ventricular development may cause migration of ectopic germ cells from the midline, which could explain the occurrence of germinomas in the off-midline structures (3).…”
Section: Discussionmentioning
confidence: 99%
“…МРТ в начальной стадии заболевания может не выявлять патологии, либо опухоль выглядит как небольшие очаги, похожие на очаги демиелинизации или ишемии. Этим обуслов-лена нередко поздняя диагностика герминомы под-корковых узлов [3,9].…”
unclassified